Evaluasi Pengalaman Pengguna Website Responsif Beyondsultra - Kartini Aprilia Pratiwi Nuzry; Erma Suryani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Tourism is a crucial sector in the economy of a region, and the use of digital technology in the tourism industry is steadily increasing. The responsiveness of a tourism website is a key factor influencing users' perceptions and experiences with the Beyondsultra website. Beyondsultra is a tourism website for Southeast Sulawesi created by the City of Kendari Regional-Owned Enterprise. The research aims to identify the responsiveness of the Beyondsultra website in influencing user perceptions of the quality of their user experience and to provide appropriate recommendations for the company to enhance user satisfaction with the Beyondsultra website. The selected respondents for the study are potential tourists and active users of the Beyondsultra website. Based on data obtained from user satisfaction observations while interacting with the Beyondsultra website using the User Experience Questionnaire (UEQ) and System Usability Scale (SUS) methods, above-average results were obtained for UEQ. Subsequently, a reevaluation was conducted to delve deeper into the issues faced by users, utilizing Cooperative Evaluation techniques. The research findings indicate an improvement in user satisfaction with the Beyondsultra website using the UEQ method, with a 68% increase in attractiveness, 93% in clarity, 91% in efficiency, 100% in stimulation, and 63% in novelty. However, one aspect, precision, remained unchanged after evaluation. In the SUS method, the average assessment score showed a 15% improvement.